Comparing dry farming of tomatoes across varieties and soil management history - Gill, Alison R.; Rainey, Coleman; Socolar, Yvonne; Gil-Santos, Yordi; Bowles, Timothy M. (Frontiers in Sustainable Food Systems, 2024)
Farmers faced with increasingly limited access to freshwater for irrigation are utilizing dry farming techniques to produce fruit, vegetable, and grain crops. Defined as crop production during a dry season using little or no irrigation, dry farming relies on water stored in the soil and requires specialized soil management, healthy soil biology, and careful selection of crop varieties. We investigated these three factors in a dry-farmed tomato (Solanum lycopersicum) field trial with three indeterminate varieties (Early Girl, Momotaro, and Zapotec) and two determinate genotypes (76R and rmc), the latter serving as a model system for studying the role of arbuscular mycorrhizal (AM) fungi. While five prior years of contrasting surface tillage practices changed soil properties, they did not affect marketable tomato yields or quality, nor affect plant physiology, including plant water use efficiency [intrinsic (WUEi) and long-term (δ13C)], gas exchange, stem water potential (Ψstem), and leaf relative water content (RWC). Early Girl produced a greater number of fruits and fewer non-marketable fruits than Momotaro and Zapotec. Although AM fungi root colonization was very low for both wildtype mycorrhizal genotype 76R and its reduced mycorrhizal mutant rmc, it differed significantly depending on genotype and tillage treatment. 76R produced slightly greater marketable fruit, but physiological responses did not differ significantly between genotypes. This study does not provide field-based evidence that soil chemical and biological changes resulting from no-till influence dry-farmed tomato productivity, while genotype had a clear impact on tomato yield and quality. Field-scale tillage experiments may better capture soil physical changes that affect water availability, especially at depth, and should be examined.